Probabilistic seismic hazard assessment for Hanoi city - Truyen, Pham The; Phuong, Nguyen Hong (Vietnam Journal of Earth Sciences, 2019)
In this study, the methodology of probabilistic seismic hazard assessment proposed by Cornell and Esteva in 1968 was applied for Hanoi city, using an earthquake catalog updated until 2018 and a comprehensive seismotectonic model of the territory of Vietnam and adjacent sea areas. Statistical methods were applied for declustering the earthquake catalog, then the maximum likelihood method was used to estimate the parameters of the Gutenberg–Richter Law and the maximum magnitude for each seismic source zone. Two GMPEs proposed by Campbell & Bozorgnia (2008) and Akkar et al., (2014) were selected for use in hazard analysis. Results of PSHA for Hanoi city are presented in the form of probabilistic seismic hazard maps, depicting peak horizontal ground acceleration (PGA) as well as 5-hertz (0.2 sec period) and 1-hertz (1.0 sec. period) spectral accelerations (SA) with 5-percent damping on a uniform firm rock site condition, with 10%, 5%, 2% and 0,5% probability of exceedance in 50 years, corresponding to return times of 475; 975; 2,475 and 9,975 years, respectively. The results of PSHA show that, for the whole territory of Hanoi city, for all four return periods, the predicted PGA values correspond to the intensity of VII to IX degrees according to the MSK-64 scale. As for the SA maps, for all four return periods, the predicted SA values at 1.0 s period correspond to the intensity of VI to VII, while the predicted SA values at 0.2 s period correspond to the intensity of VIII to X according to the MSK-64 scale. This is the last updated version of the probabilistic seismic hazard maps of Hanoi city. The 2019 probabilistic seismic hazard maps of Hanoi city display earthquake ground motions for various probability levels and can be applied in seismic provisions of building codes, insurance rate structures, risk assessments, and other public policy.